2018
DOI: 10.1016/j.jweia.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

CFD simulation of snow transport over flat, uniformly rough, open terrain: Impact of physical and computational parameters

Abstract: In the past, Computational fluid dynamics (CFD) simulations have been successfully applied for the prediction of snow drift around buildings and on building roofs. A literature study indicates that a wide range of influential computational and physical parameters exist for snow drifting predictions in CFD, while the impact of these parameters is unclear, resulting in a lack of available CFD simulation guidelines. Therefore, this study presents a systematic and generic analysis with emphasis on the fundamentals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Many studies have shown the large impact of the choice of Sc t on the resulting concentration fields (e.g. Tominaga and Stathopoulos 2007Gousseau et al 2011a;Blocken et al 2016a;Toja-Silva et al 2017;Li et al 2018;Kang et al 2018). Second-order closure is also possible for the turbulent heat and mass fluxes, but this option is not often used in CFD for building simulation.…”
Section: Reynolds-averaged Navier-stokesmentioning
confidence: 99%
“…Many studies have shown the large impact of the choice of Sc t on the resulting concentration fields (e.g. Tominaga and Stathopoulos 2007Gousseau et al 2011a;Blocken et al 2016a;Toja-Silva et al 2017;Li et al 2018;Kang et al 2018). Second-order closure is also possible for the turbulent heat and mass fluxes, but this option is not often used in CFD for building simulation.…”
Section: Reynolds-averaged Navier-stokesmentioning
confidence: 99%
“…S2. Because the height of simulation domain is only 10 m (much smaller than the thickness of atmospheric boundary layer 41 ), the shear speed at upper boundary is set to be u * (the same value at inlet) as previous study did 46 . Consequently, turbulent kinetic energy and turbulent dissipation rate wouldn’t change along the length of upper boundary 47 .…”
Section: Methodsmentioning
confidence: 99%
“…The snow transport in a suspension layer is calculated by using a convection-diffusion equation (Tominaga et al, 2011a;Zhou et al, 2016a;Zhu et al, 2017;Kang et al, 2018), in which the snow phase is considered to have the same velocity as the airflow in the horizontal direction, and a virtual velocity in the direction of gravity is added to the convection term to represent the falling of snow. The complete equation is expressed as…”
Section: Snow Transportmentioning
confidence: 99%